Association Between Hypocholesterolemia and Mortality in Critically Ill Patients With Sepsis: A Systematic Review and Meta-Analysis. (1st February 2023) - Hofmaenner, Daniel A.; Arina, Pietro; Kleyman, Anna; Page Black, Lauren; Salomao, Reinaldo; Tanaka, Sébastien; Guirgis, Faheem W.; Arulkumaran, Nishkantha; Singer, Mervyn
Abstract : OBJECTIVE: To ascertain the association between cholesterol and triglyceride levels on ICU admission and mortality in patients with sepsis. DATA SOURCES: Systematic review and meta-analysis of published studies on PubMed and Embase. STUDY SELECTION: All observational studies reporting ICU admission cholesterol and triglyceride levels in critically ill patients with sepsis were included. Authors were contacted for further data. DATA EXTRACTION: Eighteen observational studies were identified, including 1, 283 patients with a crude overall mortality of 33.3%. Data were assessed using Revman (Version 5.1, Cochrane Collaboration, Oxford, United Kingdom) and presented as mean difference (MD) with 95% CIs, p values, and I 2 values. DATA SYNTHESIS: Admission levels of total cholesterol (17 studies, 1, 204 patients; MD = 0.52 mmol/L [0.27–0.77 mmol/L]; p < 0.001; I 2 = 91%), high-density lipoprotein (HDL)-cholesterol (14 studies, 991 patients; MD = 0.08 mmol/L [0.01–0.15 mmol/L]; p = 0.02; I 2 = 61%), and low-density lipoprotein (LDL)-cholesterol (15 studies, 1, 017 patients; MD = 0.18 mmol/L [0.04–0.32 mmol/L]; p = 0.01; I 2 = 71%) were significantly lower in eventual nonsurvivors compared with survivors. No association was seen between admission triglyceride levels and mortality (15 studies, 1, 070 patients; MD = 0.00 mmol/L [–0.16 to 0.15 mmol/L]; p = –0.95; I 2 = 79%). CONCLUSIONS: Mortality was associated with lower levels of total cholesterol, HDL-cholesterol, and LDL-cholesterol, but not triglyceride levels, in patients admitted to ICU with sepsis. The impact of cholesterol replacement on patient outcomes in sepsis, particularly in at-risk groups, merits investigation.